Conservative surgery for ipsilateral breast tumor recurrence. Issue 1 (30th April 2014) - Vila, Jose; Garcia‐Etienne, Carlos A.; Vavassori, Andrea; Gentilini, Oreste; Rubio, Isabel T.; Dixon, J. Michael
<x xml:space="preserve">Abstract</x> The surgical and radiotherapeutic management of patients who develop an ipsilateral breast recurrence after primary conservative therapy remains controversial. Although current guidelines indicate the need for mastectomy for all recurrences, some reports in the literature suggest that a new conserving procedure (including repeat lumpectomy and second sentinel node biopsy) may be oncologically safe in selected patients. The rationale and current evidence for an appropriate second conservative approach are reviewed and discussed. J. Surg. Oncol. 2014 110:62–67. © 2014 Wiley Periodicals, Inc.